Women's voices, feminist visions : classic and contemporary readings / Susan M. Shaw & Janet Lee. - Shaw, Susan M.
As a leading introductory women's studies reader, Shaw and Lee's Women's Voices, Feminist Visions offers an excellent balance of classic, conceptual, and experiential selections including new contemporary readings. This student-friendly text provides short and accessible readings reflecting the diversity of women's experiences. With each new edition, the authors keep the framework essays and selections of readings fresh and interesting for students.